Enhancing Decision-Making Skills in Islamic Religious Education: A Study on Utilizing PowerPoint-Assisted Puzzle Learning with the Make a Match Model - Tatang Muh Nasir; Acep Heris Hermawan; Hasbiyallah Hasbiyallah; Hidayat Aji Permana; Eneng Dewi Siti Sobariah; Laelatul Nuroh; Didin Sahidin (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the feasibility and effectiveness of employing puzzle learning media supported by PowerPoint applications, employing the make a match model, within the context of Islamic religious education. The make a match model engages students in a pair card game to deduce answers to conceptual questions. Following the Research and Development (RD) methodology by Borg and Gall, this research aims to develop and assess the efficacy of puzzle learning media using a PowerPoint application with the make a match model, focusing on ethnic diversity material in Indonesia. The findings indicate that the puzzle learning media, supported by the PowerPoint application, attained an average material expert validity score of 3.25, media validation score of 3.78, and practitioner validation score of 3.4, suggesting its feasibility. Moreover, student responses from both limited and broad tests yielded an average score of 44, indicating an improvement in decision-making skills in Islamic religious education. The N-Gain scores of 0.5 in broad tests and 0.7 in limited tests, interpreted within the N-Gain criteria, demonstrate a significant increase, falling within the medium category. Furthermore, the t-test analysis reveals a significant difference, indicating the effectiveness of puzzle learning media supported by PowerPoint applications utilizing the make a match model as a learning medium.